Is it Truly Microteching Subject that can Push Students' Teaching Skill? - Ahmad Munawir; Alam Arya Duta Haidir (Eduvelop: Journal of English Education and Development, 2022)
The research aims to find out the perception of English Education students toward the effectiveness of microteaching subject to support their teaching skills in terms of planning for the lesson plan and classroom management. The subject of this research was the English Language Education students 2016 of Sulawesi Barat University which consist of 5 participants who were selected by using purposive sampling method. This study used qualitative method in collecting data. The researcher conducted interview by using telephone and recorded it directly due to the government’s appeal to stay at home due to the soaring of covid-19 outbreak in Indonesia. Data collection was conducted on 16th May 2020 and 18th May 2020. This study revealed that microteaching subject is effective to support the teaching skills of English Education students of Sulawesi Barat University, both in preparing learning materials and also classroom management. The findings revealed that Students of English Education of Sulawesi Barat University gained knowledge from microteaching subject in TEFL II course and they believe that microteaching subject is a great importance to prepare them to face the actual teaching process situation. The result of this research is expected to give positive contribution for education field. The findings of this research are expected to provide useful information to educators as well as students. The results can be used to enlighten parties concerned on the impact of microteaching on teaching skills.